2018
DOI: 10.1111/jomf.12478
|View full text |Cite
|
Sign up to set email alerts
|

“There Is No Perfect School”: The Complexity of School Decision‐Making Among Lesbian and Gay Adoptive Parents

Abstract: Parents influence their children's educational experiences in part via school selection. This process is particularly complex for families with multiple minority, potentially stigmatized, statuses. This qualitative study examines middle-class lesbian and gay (LG) adoptive parents' school decision-making. Parents' economic resources provided the foundation for how parents weighed child/family identities (children's race, LG-parent family structure, child's special needs) and school-related concerns (e.g., acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…Of these articles, eight name the construct of White supremacy without defining it. In these cases, the term is used to describe a structuring element and social narrative of society and research (Acosta, ; Goldberg, Allen, Black, Frost, & Manley, ; Hagerman, ; Marks, ; Purcell, Oldham, Weiser, & Sharp, ; Rockquemore & Laszloffy, ; Sharp & Weaver, ; Spencer, Mallory, Toews, Stith, & Wood, ). In four articles, White supremacy receives a more nuanced introduction as an organizing theme that has created deleterious effects for the identities and daily lives of racially diverse families (Carroll, ; Karpman, Ruppel & Torres, ; Landor & Barr, ; Willetts, ).…”
Section: White Supremacy: a Hidden Lens In Family Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Of these articles, eight name the construct of White supremacy without defining it. In these cases, the term is used to describe a structuring element and social narrative of society and research (Acosta, ; Goldberg, Allen, Black, Frost, & Manley, ; Hagerman, ; Marks, ; Purcell, Oldham, Weiser, & Sharp, ; Rockquemore & Laszloffy, ; Sharp & Weaver, ; Spencer, Mallory, Toews, Stith, & Wood, ). In four articles, White supremacy receives a more nuanced introduction as an organizing theme that has created deleterious effects for the identities and daily lives of racially diverse families (Carroll, ; Karpman, Ruppel & Torres, ; Landor & Barr, ; Willetts, ).…”
Section: White Supremacy: a Hidden Lens In Family Sciencementioning
confidence: 99%
“…Of these articles, eight name the construct of White supremacy without defining it. In these cases, the term is used to describe a structuring element and social narrative of society and research (Acosta, 2018;Goldberg, Allen, Black, Frost, & Manley, 2018;Hagerman, 2017;Marks, 2000;Purcell, Oldham, Weiser, & Sharp, 2017;Rockquemore & Laszloffy, 2003;Sharp & Weaver, 2015;Spencer, Mallory, Toews, Stith, & Wood, 2017).…”
Section: White Supremacy: a Hidden Lens In Family Sciencementioning
confidence: 99%
“…Yet there is reason to believe that victimization might intersect with or vary according to where families live or the types of schools children attenddimensions that have generally not been explored quantitatively. A qualitative study found that LG-parent families living in rural and politically conservative communities encountered unique challenges in school selection, amidst implicit and explicit biases against their families (Goldberg et al, 2018). Thus, it is worth considering community factors in exploring children's exposure to victimization.…”
Section: Family Structure As a Predictor Of Victimizationmentioning
confidence: 99%
“…Although research has gradually begun to address the experiences of LGparent families (Goldberg, 2010), rarely has it considered their intersections with the school context. Studies of LG parents of young children have examined their school decisions (Goldberg et al, 2018) and school involvement (Goldberg and Smith, 2014;Goldberg et al, 2017) and several studies of LG-parent families with school-aged children have explored children's experiences with teasing and victimization (Bos and van Balen, 2008;Kosciw and Diaz, 2008;Rivers et al, 2008;Farr et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Parents influence their children's educational experiences in part via school selection. This process is particularly complicated for families with multiple minorities, potentially stigmatized statuses (Goldberg, et. Al., 2018).…”
Section: Lifestylementioning
confidence: 99%